Accompanimeter 1.0: creation and initial field testing of a tool to assess the extent to which the principles and building blocks of accompaniment are present in community health worker programs. Issue 1 (1st January 2019) - Carrasco, Hector; Napier, Harriet; Giber, David; Kang, Stephanie; Aguerreberre, Mercedes; Hing, Matthew; Silva, Vinicius Siqueira Tavares Meira; Montaño, Mariana; Perry, Henry; Palazuelos, Daniel
ABSTRACT: Background : The strategic incorporation of community health workers (CHWs) into health system strengthening efforts is recognized as a critical and high-value approach for meeting the Sustainable Development Goals established by the United Nations in 2015. How to best build CHW programs, however, is prone to a wide variety of opinions and philosophies, many of which are often externally imposed. Partners in Health (PIH) is a non-governmental organization that pioneered an approach to healthcare system strengthening, called accompaniment, in which CHWs play a key role. Learning from PIH is a critical first step in replicating the organization's achievements beyond PIH. As such, PIH has developed a tool, referred to as the 'Accompanimeter 1.0, ' that serves to evaluate existing CHW programs and guide adjustments in programming. Objective : To provide a standardized approach for defining, assessing, and implementing accompaniment in CHW programs using a tool called the Accompanimeter 1.0. Methods : Development of this tool included three stages: (1) desk review of literature relevant to the work of CHWs globally, (2) discussions among colleagues and initial field testing, (3) feedback from colleagues who are experts in community health and in the principles of accompaniment. Results : Three core principles of accompaniment in a CHW program were identified: professionalization, CHWs as bridges to institutional strength, and community proximity . These core principles direct five thematic areas that are found in successful CHW programs: Partnering (co-creating engagement with a continuous and intersectoral dialogue to improve the program); Choosing (identifying the right people for the right job); Educating (building CHWs´ capacity); Incentivizing (enabling CHWs to perform their work without financial sacrifice); Supervising (mentoring CHWs for personal growth). Conclusions : The Accompanimeter 1.0 can serve as a helpful tool for CHW program implementation and policy decisions that maximize system-side inputs, community engagement, and support for individuals with medical issues.